Photography and the social short film as research instruments: didactic experiences - Rodríguez-Puertas, Rubén (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
We currently live in an intensely visual society, however, from the Social Sciences the image is despised as a didactic and research tool, leaving it relegated to the world of the arts. With this background question, we want to show the experience of the students of the subjects: Society, Family and Education, and Sociology of Education (from the University of Almería), after the use of photography and the social short film as complementary didactic instruments to the investigation. Thus, the training experiences of these students will be shown after the use of these resources in their projects.